Tratti, orientamenti motivazionali e prestazione in un'agenzia per il lavoro: un contributo empirico - Dello Russo, S.; Vecchione M.; Borgogni L. (Rassegna di Psicologia, 2007)
The aim of this paper is to identify personality traits and motivational characteristics associated with organizational success in order to have a guide for recruiting programs. The study involved the whole population of a temporary work agency (N = 233), who was asked to fill in two questionnaires assessing personality traits (Big Five Questionnaire, Caprara, Barbaranelli & Borgogni, 1993) and motivational orientations (T.O.M. – Test of Motivational Orientation, Petitta, Borgogni & Mastrorilli, 2005). Three groups of subjects defined as “best”, “medium”, and “low performers” on the basis of annual performance appraisal, were compared with reference to the above characteristics. The results show significant differences between best and low performers in Conscientiousness and Emotional Stability. Relations between personality traits and job performance hold across time and job positions. Significant differences in traits and motives among different job positions were also found.